Tunable PID Controller from the WinCC Unified Interface via OPC UA - Carbajal Morán, Hipólito (2024)
Abstract—In this study, it was sought to implement a Proportional-Integral-Derivative (PID) controller in SIMATIC S7-1500 Programmer Logic Controller (PLC) with Open Platform Communications United Architecture (OPC UA) communication and tunable control from WinCC unified, in order to reduce the settling time of the temperature variable in the plant SO 3536-8T. Using the Ziegler-Nichols PID rule, adjustments were made to the Kp,Ti and Td coefficients of the PID controller. Initially set with values of Kp = 1.0, Ti = 20.00 s, Td = 0.1 s, and ess ≤ 2%. Without tuning, a maximum settling time of 193 s was achieved for a setpoint of 50 °C. After tuning from the WinCC unified interface, improved parameters (Kp = 6.05, Ti= 0.75 s, Td = 0.15 s) were obtained for ess ≤ 2%, presenting an underdamped response and a maximum settling time of 54 s. The tests present a reduction of the settling time of the variable higher than 60.25%, evidencing the effectiveness of the tunable PID controller in improving the system performance. Overall, the successful implementation of this tunable PID controller not only optimized the efficiency of the control system, but also provided a considerable reduction in the settling time of the temperature variable in the plant, representing a significant advance for the operation and overall efficiency of the process.